Synthesis of the Major Bacteriophage f1 Coat Protein - Smilowitz, Henry (1971)
A method which allows one to follow the synthesis of the major f1 coat protein in normal, unirradiated f1-infected cells is reported. The N-terminal tryptic peptide of this protein, labeled with (14)C-lysine, has a negative charge at pH 4.5 and is readily separated from the contaminating peptides of host cell proteins. This technique was used to study several aspects of the synthesis of the major f1 coat protein in infected cells.